Layered clay mineral-based vulcanized polyacrylonitrile positive electrode material as well as preparation method and application thereof
By using the interlayer nano-limited domain effect of layered clay minerals for in-situ polymerization and combining with sublimated sulfur powder, the problems of poor cycling performance and collapse of the positive electrode structure during charging and discharging of lithium-sulfur batteries are solved, and a high ratio is achieved Vulcanized polyacrylonitrile positive electrode material with capacity, good rate performance and good cycle performance.
Patent Information
- Application Number
- CN202411531220.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
AI Technical Summary
Traditional lithium-sulfur batteries have poor circulation performance due to the polysulfide shuttle effect during charging and discharging, and the volume expansion of the vulcanized polyacrylonitrile positive electrode material during charging and discharging, which is prone to collapse of the positive electrode structure.
The layered clay mineral-based sulfated polyacrylonitrile positive electrode material is used to realize the in-situ polymerization of acrylonitrile monomers through the interlayer nano-limited domain effect of layered clay minerals, and calcination is carried out in combination with sublimation sulfur powder to form a stable sulfur-sulfur structure. , alleviate volume expansion and stress changes.
It significantly improves the structural stability of vulcanized polyacrylonitrile, extends the cycle life of the electrode, avoids electrode collapse, and improves the cycle performance and rate performance of lithium-sulfur batteries.
Smart Images

Figure CN119400826A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials, and in particular to a layered clay mineral-based sulfide polyacrylonitrile positive electrode material and a preparation method and application thereof. Background Art
[0002] Traditional lithium-sulfur batteries will experience polysulfide shuttle effect during the charge and discharge process, resulting in poor battery cycle performance, which is a key scientific issue restricting the large-scale commercial application of lithium-sulfur batteries. Sulfurized polyacrylonitrile (SPAN) as a positive electrode material undergoes solid-solid transformation during the charge and discharge process and does not produce soluble polysulfides. Compared with traditional lithium-sulfur batteries, Li-SPAN batteries have higher discharge specific capacity and better cycle performance, and are currently an effective material for solving the shuttle effect. However, the internal stress of sulfurized polyacrylonitrile changes greatly during the charge and discharge process, and the electrode volume expands significantly, which can easily cause the positive electrode structure to collapse. Summary of the invention
[0003] The purpose of the present invention is to address the above-mentioned deficiencies in the prior art and to provide a layered clay mineral-based sulfide polyacrylonitrile positive electrode material and a preparation method and application thereof.
[0004] The present invention provides a method for preparing a layered clay mineral-based sulfide polyacrylonitrile positive electrode material, comprising the following steps:
[0005] Adding acrylonitrile and a polymerization initiator to a layered clay mineral dispersion, stirring in a water bath for reaction, and then centrifuging and vacuum drying to obtain a polyacrylonitrile / mineral solid;
[0006] The polyacrylonitrile / mineral solid and sublimated sulfur powder are mixed and ground, and then calcined at 300-600° C. in a protective atmosphere to obtain a layered clay mineral-based sulfided polyacrylonitrile positive electrode material.
[0007] Furthermore, the mass ratio of the mineral to acrylonitrile is 1:9-15.
[0008] Furthermore, the layered clay mineral is one or more of montmorillonite, biotite, kaolinite, vermiculite, attapulgite and rectorite.
[0009] Furthermore, the polymerization initiator is azobisisobutyronitrile.
[0010] Furthermore, the mass ratio of the polymerization initiator to acrylonitrile is 0.01-0.05:1.
[0011] Furthermore, the mass ratio of the polyacrylonitrile / mineral solid to the sublimated sulfur powder is 1:2-4.
[0012] Further, the reaction was vigorously stirred in a 70°C water bath for 2 h.
[0013] Furthermore, sodium hydroxide solution is added to commercial acrylonitrile, and after the solution is allowed to stand and separate into layers, the lower layer of sodium hydroxide is discarded to obtain acrylonitrile from which the polymerization inhibitor has been removed.
[0014] Furthermore, the protective atmosphere is nitrogen.
[0015] A layered clay mineral-based sulfided polyacrylonitrile positive electrode material prepared by the above-mentioned preparation method.
[0016] A lithium-sulfur battery comprises the above-mentioned layered clay mineral-based sulfided polyacrylonitrile positive electrode material.
[0017] The present invention utilizes the interlayer nano-confinement effect of layered clay minerals to realize the in-situ polymerization of acrylonitrile monomers, and mixes the polymerized composite material with sublimated sulfur powder for calcination; on the one hand, the interlayer confinement effect of layered clay minerals makes the polymerization process more controllable and will not agglomerate, and the polyacrylonitrile formed by the confinement effect can be more tightly and fully combined with the sublimated sulfur during the subsequent calcination process; on the other hand, the nano-space between the layers of layered clay minerals can also alleviate the huge volume expansion and stress changes of the sulfided polyacrylonitrile during the charging and discharging process, and alleviate the expansion of the electrode from collapse. The present invention uses the interlayer nano-confinement effect of layered clay minerals to perform in-situ polymerization of acrylonitrile, which can significantly improve the structural stability of the sulfided polyacrylonitrile, and will not cause electrode collapse after multiple cycles.
[0018] The present invention utilizes the nano-confinement effect of layered clay minerals to prepare a montmorillonite-based sulfided polyacrylonitrile positive electrode material that can be used in lithium-sulfur batteries and has high specific capacity, good rate performance, and good cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The XRD patterns of montmorillonite, polyacrylonitrile / montmorillonite and sulfide polyacrylonitrile / montmorillonite in Example 1;
[0020] Figure 2 It is the infrared spectrum of SPAN / MMT;
[0021] Figure 3 It is the XPS image of SPAN / MMT;
[0022] Figure 4 is the SEM image of SPAN / MMT;
[0023] Figure 5 It is the energy spectrum of SPAN / MMT;
[0024] Figure 6 is the 0.4A / g cycle performance diagram of Example 1;
[0025] Figure 7 3A / g cycle performance diagram of Example 1;
[0026] Figure 8 is the rate performance diagram of Example 1;
[0027] Fig. 9 This is the 0.2A / g cycle performance diagram of Comparative Example 1;
[0028] Fig.10 1A / g cycle performance diagram of Comparative Example 1;
[0029] Fig.11 This is the 0.2A / g cycle performance diagram of Comparative Example 2;
[0030] Fig.12 This is the 1A / g cycle performance diagram of Comparative Example 2. DETAILED DESCRIPTION
[0031] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.
[0032] Example 1
[0033] Step 1: Take 6.25mL of acrylonitrile and add 1mL of 1mol / L sodium hydroxide solution, stir, pour into a separatory funnel, wait for the solution to stand and separate, pour off the lower layer of sodium hydroxide, and obtain acrylonitrile with polymerization inhibitor removed. Take 0.5g of montmorillonite and dissolve it in 100mL of deionized water, stir it at high speed magnetically for 1h, and then ultrasonicate it for 1h, repeat this process 6 times to make the montmorillonite fully dispersed. Add 6.25mL of acrylonitrile solution with polymerization inhibitor removed (mass ratio of montmorillonite to acrylonitrile is 1:10) to the montmorillonite dispersion, ultrasonicate it for 1h, then add 75mg of azobisisobutyronitrile as a polymerization initiator, and stir vigorously in a 70℃ water bath for 2h. Centrifuge after reaction, and vacuum dry it at 80℃ to obtain polyacrylonitrile / montmorillonite solid.
[0034] Step 2: Mix 0.5 g of polyacrylonitrile / montmorillonite solid obtained in the first step with 1.5 g of sublimated sulfur powder and grind them for 30 minutes into powder. Put it into a porcelain boat, cover it with a lid, and heat it to 300°C at a heating rate of 2°C / min in a nitrogen environment of a tubular furnace. Keep it warm for 300 minutes. After the reaction is completed, collect the resulting powder, which is the sulfide polyacrylonitrile / montmorillonite material.
[0035] Montmorillonite is a layered clay mineral whose main component is aluminum silicate. The layered structure is composed of aluminum oxide octahedron in the middle and silicon oxide tetrahedron above and below. The interlayers of montmorillonite have adsorption capacity, and the interlayer spacing will expand after adsorption. During in-situ polymerization, acrylonitrile will enter the interlayers of montmorillonite. Under the action of the polymerization initiator azobisisobutyronitrile, acrylonitrile will polymerize in the interlayers of montmorillonite to form polyacrylonitrile.
[0036] Example 2
[0037] The difference between the embodiment 1 and the example 1 is that the mass ratio of montmorillonite to acrylonitrile in step 1 is 1:12. The other steps are the same as those in the example 1.
[0038] Example 3
[0039] The difference between the embodiment and Example 1 is that the mass ratio of montmorillonite to acrylonitrile in step 1 is 1:15. The other steps are consistent with Example 1.
[0040] Example 4
[0041] The implementation method is different from Example 1 in that the layered clay mineral in step 1 is one of biotite, kaolinite, vermiculite, attapulgite and rectorite.
[0042] Comparative Example 1
[0043] The difference between the embodiment 1 and the example 1 is that the mass ratio of montmorillonite to acrylonitrile in step 1 is 1:5. The other steps are consistent with the example 1.
[0044] Comparative Example 2
[0045] The implementation method is different from Example 1 in that montmorillonite is not added in step 1. The other steps are consistent with Example 1.
[0046] Electrode sheet preparation and battery assembly:
[0047] The electrochemical performance of montmorillonite-based sulfurized polyacrylonitrile electrode materials was tested by assembling button half-cells. Electrode slurry was prepared using aqueous binder sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR). The materials with a mass ratio of positive electrode material: conductive carbon black: CMC: SBR = 7:2:0.5:0.5 were weighed, and an appropriate amount of ultrapure water was added to mix thoroughly and evenly coated on aluminum foil, and dried in a blast drying oven at 80℃ for 10h. Then, circular electrode sheets with a diameter of 10mm were cut to assemble button cells, in which the lithium sheet was the negative electrode, the separator was Celgard 2500, and the electrolyte was 1M LiPF6 in EC:DEC = 1:1Vol%. The oxygen and moisture contents in the glove box were both less than 0.1ppm, the test current density was 0.4A / g, and the test voltage range was 1-3V.
[0048] The polyacrylonitrile / montmorillonite material prepared in Example 1 was used as the positive electrode material and assembled into a button cell. The charge and discharge cycle test was carried out at 25°C, a voltage range of 1 to 3V, and a current density of 0.4A / g. The reversible capacity of the cell was 1540mAh g -1 When the discharge rate is 3A / g, the discharge capacity is 1291mAh g after 300 cycles. -1 , and the Coulomb efficiency remains basically at 100% from the second cycle onwards.
[0049] Figure 1 The XRD diagrams of montmorillonite, polyacrylonitrile / montmorillonite and sulfide polyacrylonitrile / montmorillonite in Example 1 show that the (001) peak of montmorillonite after in-situ polymerization moves to the left compared with that before the reaction, indicating that polyacrylonitrile is indeed composited between montmorillonite layers.
[0050] Figure 2 This is the infrared spectrum of SPAN / MMT. While retaining the CN double bond, a CS bond also appeared, which is consistent with the conclusions of other researchers and can indicate that SPAN was successfully synthesized. Figure 3 The XPS image of SPAN / MMT is shown in the figure, where the peak at 161.7 eV corresponds to the CS bond, the peak at 163.3 eV corresponds to the CS bond formed by the short chain S and C, and the peak at 164.6 eV corresponds to the SS bond. Together with the infrared results, it proves the successful synthesis of SPAN.
[0051] Figure 4 and 5 This is the SEM photo and energy spectrum of SPAN / MMT. In the photo, we can see that the sample as a whole still has the layered structure of montmorillonite, which indicates that the in-situ polymerization process did not destroy the structure of montmorillonite. The energy spectrum shows that the Al, Si, O elements representing montmorillonite and the C, S, N elements representing SPAN are distributed very evenly, which means that SPAN was successfully synthesized and evenly distributed between the MMT layers.
[0052] Figure 6 This is the 0.4A / g cycle performance diagram of Example 1. -1 The reversible capacity of the battery is 1540 mAh g -1 After 100 cycles, the discharge capacity is 1491 mAh g -1 , the capacity retention rate is 96.8%.
[0053] Figure 7 3A / g cycle performance diagram of Example 1, current density is 3A g -1 After 300 cycles, the discharge capacity is 1291 mAh g -1 , the capacity retention rate is 84.2%. The cycle performance is good.
[0054] Figure 8 is the rate performance diagram of Example 1, from Figure 8 It can be seen that when the current density is restored, the battery capacity can basically return to 99% of the initial capacity, which proves the good rate performance of the battery.
[0055] The sulphurized polyacrylonitrile / montmorillonite material prepared in Comparative Example 1 was used as the positive electrode material and assembled into a button cell.
[0056] Fig. 9 and Fig.10 The cycle curve is shown when the mass ratio of montmorillonite to acrylonitrile is 1:5 (Comparative Example 1). When the relative content of montmorillonite increases, the conductivity of the electrode is also poor due to the poor conductivity of the mineral itself, which slows down the electrochemical process and reduces the capacity. Figure 7 and Figure 8 The discharge capacity of Comparative Example 2 is very low, much lower than that of Example 1.
[0057] The sulphurized polyacrylonitrile prepared in Comparative Example 2 was used as the positive electrode material and assembled into button cells.
[0058] like Fig.11 and Fig.12 This is the cycle curve of comparative example 2. When montmorillonite is not added, the positive electrode material lacks carrier support, and the electrode is prone to collapse after multiple cycles. Fig.11 It can be seen that the capacity retention rate is high in the first 50 cycles, but the subsequent electrode structure collapses, resulting in capacity decay. Fig.12 When cycling at a higher current density, more obvious capacity decay can be seen.
[0059] In summary, the montmorillonite-based polyacrylonitrile sulfide positive electrode material prepared in Example 1 of the present invention is compared with polyacrylonitrile not polymerized by the nanoconfinement of montmorillonite. The polyacrylonitrile formed by the confinement effect can be more closely and fully combined with sublimated sulfur during the subsequent calcination process, and the nanospace between the montmorillonite layers can also alleviate the huge volume expansion and stress changes of the polyacrylonitrile sulfide during the charge and discharge process. Therefore, in-situ polymerization of acrylonitrile by means of the interlayer nanoconfinement effect of montmorillonite can significantly improve the structural stability of polyacrylonitrile sulfide, and the electrode will not collapse after multiple cycles.
[0060] The montmorillonite-based sulfide polyacrylonitrile positive electrode material prepared in Example 1 of the present invention has a stable structure and therefore has excellent cycle performance. The present invention utilizes the nano-confinement effect of montmorillonite to prepare a montmorillonite-based sulfide polyacrylonitrile positive electrode material with high specific capacity, good rate performance, and good cycle performance.
[0061] For matters not mentioned above, the prior art applies.
[0062] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a layered clay mineral-based sulfide polyacrylonitrile positive electrode material, characterized in that: The steps include: Adding acrylonitrile and a polymerization initiator to a layered clay mineral dispersion, stirring in a water bath for reaction, and then centrifuging and vacuum drying to obtain a polyacrylonitrile / mineral solid; The polyacrylonitrile / mineral solid and sublimated sulfur powder are mixed and ground, and then calcined at 300-600° C. in a nitrogen environment to obtain a layered clay mineral-based sulfurized polyacrylonitrile positive electrode material.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the layered clay mineral to acrylonitrile is 1:9-15.
3. The preparation method according to claim 1, characterized in that: The layered clay mineral is one or more of montmorillonite, biotite, kaolinite, vermiculite, attapulgite and rectorite.
4. The preparation method according to claim 1, characterized in that: The polymerization initiator is azobisisobutyronitrile; the mass ratio of the polymerization initiator to acrylonitrile is 0.01-0.05:
1.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the polyacrylonitrile / mineral solid to sublimated sulfur powder is 1:2-4.
6. The preparation method according to claim 1, characterized in that: The reaction was stirred vigorously in a 70 °C water bath for 2 h.
7. The preparation method according to claim 1, characterized in that: Sodium hydroxide solution is added to commercial acrylonitrile, and after the solution is allowed to stand and separate into layers, the lower layer of sodium hydroxide is discarded to obtain acrylonitrile from which polymerization inhibitors have been removed.
8. The preparation method according to claim 1, characterized in that: The protective atmosphere was nitrogen.
9. A layered clay mineral-based sulfide polyacrylonitrile positive electrode material prepared by the preparation method according to any one of claims 1 to 8.
10. A lithium-sulfur battery, characterized in that: It comprises the layered clay mineral-based sulfide polyacrylonitrile positive electrode material as claimed in claim 9.
Citation Information
Patent Citations
Battery diaphragm modification layer material, diaphragm and lithium-sulfur battery
CN112271404A
Preparation method of sulfur modified polyacrylonitrile material
CN113830738A
Vulcanized polyacrylonitrile material, lithium-sulfur battery positive electrode thereof and lithium-sulfur battery
CN115304797A
Preparation method of clay mineral nanocomposite / polymer composite solid electrolyte with high room-temperature ionic conductivity
CN116799299A